2004
DOI: 10.1002/bip.20014
|View full text |Cite
|
Sign up to set email alerts
|

1,1,1,3,3,3‐hexafluoroisopropanol induced thermal unfolding and molten globule state of bovine α‐lactalbumin: Calorimetric and spectroscopic studies

Abstract: The thermal denaturation of alpha-lactalbumin was studied at pH 7.0 and 9.0 in aqueous 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) by high-sensitivity differential scanning calorimetry. The conformation of the protein was analyzed by a combination of fluorescence and circular dichroism measurements. The most obvious effect of HFIP was lowering of the transition temperature with an increase in the concentration of the alcohol up to 0.30M, beyond which no calorimetric transition was observed. Up to 0.30M HFIP the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 104 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…However, it is also known that a negative contribution from the exposure of the polar groups is expected to offset partially the positive contribution (DC pol < 0; DC apolar > 0) [29,30]. In the absence of any additive, the value of DC p for a-lactalbumin is known to be (4.6 ± 0.3) kJ Á K À1 Á mol À1 [16]. Lowering the value of DC p for a-lactalbumin under these experimental conditions indicates enhanced hydrophobic interactions between the non-polar regions of the unfolded protein and the alkyl groups of isopropanol and -CF 3 groups of HFIP, respectively, leading to reduction of the extent of reordering of water molecules surrounding the hydrophobic regions of the protein.…”
Section: Uv-visible Experimentsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it is also known that a negative contribution from the exposure of the polar groups is expected to offset partially the positive contribution (DC pol < 0; DC apolar > 0) [29,30]. In the absence of any additive, the value of DC p for a-lactalbumin is known to be (4.6 ± 0.3) kJ Á K À1 Á mol À1 [16]. Lowering the value of DC p for a-lactalbumin under these experimental conditions indicates enhanced hydrophobic interactions between the non-polar regions of the unfolded protein and the alkyl groups of isopropanol and -CF 3 groups of HFIP, respectively, leading to reduction of the extent of reordering of water molecules surrounding the hydrophobic regions of the protein.…”
Section: Uv-visible Experimentsmentioning
confidence: 95%
“…This is also supported by our fluorescence experiments where a very low intensity of binding is observed. The sulphonate group of ANS could possibly be forming an ion pair with guanidine group of GndSCN, leading to a lesser TABLE 7 Association constant (K), enthalpy (DH), and entropy (DS) of binding of ANS to a-lactalbumin in the presence of the 0.25 mol Á dm À3 (HFIP + GndSCN) equimolar mixture and 0.85 mol Á dm À3 (isopropanol + GndSCN) equimolar mixture at pH 7.0 and T = 298.15 K according to two sequential binding sites model described by equations (15) and (16) 0.25 mol Á dm À3 (HFIP + GndSCN) 0.85 mol Á dm À3 (isopropanol + GndSCN)…”
Section: Possible Binding Sites For Ansmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al 38 further suggested that the thermodynamic parameters obtained for the intermediate state of a-LA 36 are consistent with the presence of a sizeable hydrophobic core and a significant amount of secondary structure and reported that some MG-states do indeed undergo cooperative thermal transition and they are enthalpically different from the unfolded and N-states. Based upon the differential scanning calorimetric and ultraviolet (UV)-visible thermal unfolding studies of a-LA 39 and concanavalin A, 40 we have observed that the MG-state of these proteins do not show any endotherm in the entire range of the thermal scans. These observations match the findings that the MG-states do not undergo cooperative thermal transitions to the D-state.…”
Section: And Various Temperaturesmentioning
confidence: 95%
“…The DC p of native a-LA is 4.7 ± 0.3 kJ K À1 mol À1 [35]. Assuming that both polar and apolar accessible surface areas do not change significantly, the overall increase in the DC p in the presence of HTAB and SDS may be attributed to the enhanced hydrophobic interactions between the non-polar regions of the unfolded proteins and the alkyl groups of HTAB and SDS preceded by drastic exposure of the apolar accessible surface area.…”
Section: Thermal Denaturation Experimentsmentioning
confidence: 96%